Phytochemical, toxicity and antiplasmodial properties of Malaysian plectranthus amboinicus (spreng) leaves extract on plasmodium berghei - Norazsida binti Ramli (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
The search for new antimalarials is a continuing effort as the resistance to current antimalarial drugs occur one after another. Thus this study aims to discover a potential antimalarial in the Malaysian local plant. Plectranthus amboinicus is selected as a candidate for antimalarial study. There were four phases involved throughout this study. Phase one focused on the phytochemical screening of ethanolic extract and essential oil of P. amboinicus leaves. The phytochemical screening of the extracts was conducted according to the qualitative phytochemical screening test and Gas Chromatography Mass Spectrometry (GC-MS). Phytochemical screening revealed the presence of flavonoids (in the crude ethanolic extract), carvacrol (85.14 %), thymoquinone (1.65 %), terpinen-4-ol (0.7 %), octenol (0.62 %), thymol (0.23 %), and dioctylazelate (0.15 %) (in the essential oil). Phase two of the study focussed to evaluate the toxicity status of the experimenting extracts prior to conducting antimalarial study on mice infected with Plasmodium berghei. Acute oral toxicity test was conducted according to the OECD guidelines for the testing of chemicals, acute oral toxicity, limit test-acute toxic class method sections 423. Toxicity study with crude ethanolic extracts of P. amboinicus leaves revealed no toxic effect on the mice administered. The acute oral LD50 was found to be above 5000 mg/kg suggesting it to be safe for consumption. Testing with the essential oil also revealed no signs of toxicity and mortality although histopathology results showed the presence of glomerular apoptosis in kidney and evidence of central venous dilation in the liver. Thus, the LD50 was suggested as above 2000 µL/kg. Phase three focused to determine the antimalarial properties of the crude ethanolic extract and essential oil of P. amboinicus leaves. There were three important antimalarial tests that were performed on both the extracts prepared, namely prophylactic test, suppression test and curability test. An antimalarial study on the crude ethanolic extract showed no reduction of parasitemia of mice infected with P. berghei was seen in the suppressive and curative test, but pronounced reduction of parasitemia in the prophylactic test. The best dose of ethanolic extract was found to be 400 mg/kg which reduced parasitemia by 90.74 %. In contrast, the essential oil of P. amboinicus leaves not only possess some potential as a prophylaxis agent, but also a curative agent, but with a less parasitemia reduction compared to the ethanolic extract. The best prophylaxis dose was found to be 1000 µL/kg with 58.26 % reduction in parasitemia, while the best curative dose was also 1000 µL/kg with a reduction of parasitemia of 65.38 %. Similar to crude extract, no reduction of parasitemia was found in the suppression test of the essential oil. Phase four of the study focused on prophylactic test of partitioned fractions of crude ethanolic extract since the extract showed better reduction of parasitemia compared to an essential oil. The extract was partitioned with 3 different polarities of solvent to yield hexane, ethyl acetate and butane fractions. The prophylactic test on the partitioned fractions of the selective crude extract revealed hexane fraction (with 85.54 % chemo suppression) as the best prophylaxis agent, followed by the butane fraction (with 56.56 % chemo suppression) and ethyl acetate fraction (with 47.72 % chemo suppression). In all fractions 400 mg/kg was the most effective dose as prophylaxis agent. Based on these results, it can be concluded that crude extract shows better prophylaxis effect compared to fraction. P. amboinicus leaves extract shows promise as a new potential antimalarial candidate.